A Model of Wolio Language Maintenance Strategies in Society 5.0 - Firman Alamsyah Mansyur; Arsad; Asrul Nazar; Isti’anatul Hikmah; Zilani (Hasanuddin University, 2022)
This study aims to describe the Wolio language maintenance strategy model in the 5.0 era of society. This study uses qualitative research methods within the scope of sociolinguistic studies. Data were collected through library studies, and field studies. The results of this study describe five models of strategies for maintaining the Wolio language as a mother tongue, namely: 1) strengthening the preservation of Wolio customs and culture, 2) strengthening the role of Wolio traditional and cultural institutions, 3) strengthening the role of government, 4) strengthening the role of the family, and 5) strengthening the use of the latest communication and social media. The results of this study indicate that language maintenance in era 5.0 still requires the involvement of various elements, the government, the community, parents, and traditional leaders. In addition, language maintenance must be carried out by maintaining community traditions and customs because languages ​​that lose their culture will die slowly, and traditional traditions that lose their language will lose their sacredness. The use of the latest social media is also very important in maintaining language to respond to the 4.0 revolution. If not, the language will begin to be abandoned by its speakers, especially the younger generation, because they are considered inflexible, not prestige and left behind, or old-fashioned..